Penyelesaian Wanprestasi simpan Pinjam pada Koperasi danu Artha - Ida Bagus Gede Krismantara Manuaba; Anak Agung Sagung Laksmi Dewim; Ni Made Puspasutari Ujianti (Jurnal Preferensi Hukum, 2021)
Cooperatives as pillars of the national economy are not only expected to be equal to other economic actors, namely BUMN and private sectors but also have a greater role in running an economy characterized by democracy. Legal protection is all forms of efforts to protect human dignity and human rights in the field of law. Legal protection is all forms of efforts to protect human dignity and human rights in the field of law. APS is the designation given to the grouping of dispute resolution through the process of negotiation, mediation, conciliation, and expert rights. This study aimed to examine the legal protections for the parties in the event of a default in the Danu Artha Cooperative and reveal how to resolve the parties who enter into an agreement if there is a default in the Danu Artha Cooperative. This study was designed using empirical research with a sociological approach, regulations, conceptual problems, and cases. The data sources used were primary and secondary data. The results of the study revealed that legal protection in the agreement in cooperatives is important and is the basis for cooperatives in running the cooperative business, and dispute resolution against parties who default is carried out through non-litigation and litigation channels. The non-litigation route did not find a common ground so that the dispute was brought and resolved at the State Receivables and Auctions Agency.